Optimization of ingredients and processing parameters for the development of Cheddar cheese based beverage - Nikunj Sharma, Ashutosh Upadhyay , Syed Mansha Rafiq , Syed Insha Rafiq (Indian Journal of Dairy Science, 2023)
The present study was carried out to develop Cheddar cheese based beverage by optimizing the level of ingredients and the processing parameters to meet the increasing consumer demand for functional foods. Cheddar cheese (5-6 months ripened) was used for the preparation.  The effect of varying the Cheddar cheese to water ratios (1:1, 1:2 and 1:3) along with different type of emulsifying salts, TSC (tri-sodium citrate) and STPP (sodium tri-polyphosphate) and processing parameters like cooking time (4 & 6 min) and stages of water addition (2 & 3 times) on the moisture, viscosity and sensory properties of the developed beverage were studied. At cheese to water ratio of 1:3 fat separation was found to occur even after using tri-sodium citrate and sodium tri-polyphosphate as emulsifiers at all processing conditions. Cheese to water ratio of 1:1 resulted in highly viscous product. At cheese to water ratio of 1:2 it was found that the type of emulsifier used, cooking time and stages of water addition had a significant (p